Young men in Israeli haredi yeshiva education : the scholars' enclave in unrest. - Hakak, Yohai (Jewish identities in a changing world ;, 2012)
By looking at the case of Lithuanian yeshivas in Israel, Yohai Hakak’s book explores the internal tensions and dynamics of religious orders during a stage of a relative ‘loss of charisma’, in which the enthusiasm of the founding generation has diminished. It is the first study to include participant observations conducted within these institutions, which are the sacred heart of this segregated and highly religious community. The book highlights the current crisis these fundamentalist institutions are going through marked by a dramatic growth in yeshiva dropout rates. It examines the new and innovative ways the rabbis are trying to respond to the crisis. As part of these attempts the rabbinical discourse portrays a unique utopian and egalitarian world governed by supernatural forces and unlimited spiritual resources and incorporates Western psychological and democratic ideas -- Présentation de l'éditeur.